2014
DOI: 10.1200/jco.2014.32.3_suppl.205
|View full text |Cite
|
Sign up to set email alerts
|

ERBB2 gene as a potential therapeutic target in small bowel adenocarcinoma.

Abstract: 205 Background: Small bowel adenocarcinoma (SBA) is an aggressive tumor responsible for poor outcomes with an expected median OS at 5 years inferior to 30%. Because of its low incidence, few prospective studies have been performed leading to insufficient knowledge and absence of standard of care. Aiming to better understand the small bowel carcinogenesis process we screened for somatic mutations a large data set of patients in more than 740 mutational hotspots among 46 genes. Methods: In total, 83 SBA cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…Although a few previous studies of small intestinal adenocarcinomas have examined KRAS and/or BRAF mutations, which are well-known oncogenes in colorectal cancer, most of these analyses were performed on small numbers of patients (Table 9). 1,3,[10][11][12][13][14][15][16][17][18][19][20] The frequency of KRAS mutations among small intestinal adenocarcinomas ranged from 9 to 83% in the previous studies. Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a few previous studies of small intestinal adenocarcinomas have examined KRAS and/or BRAF mutations, which are well-known oncogenes in colorectal cancer, most of these analyses were performed on small numbers of patients (Table 9). 1,3,[10][11][12][13][14][15][16][17][18][19][20] The frequency of KRAS mutations among small intestinal adenocarcinomas ranged from 9 to 83% in the previous studies. Previous studies from Japan with homogeneous ethnic groups showed a wide range of frequencies of KRAS mutation (9-71%), [13][14][15]19 and other studies with heterogeneous ethnic groups, such as studies from USA, also reported various frequencies of KRAS mutation (14-83%).…”
Section: Discussionmentioning
confidence: 99%
“…Several different techniques for detecting KRAS and/or BRAF mutation were used, including restriction fragment length polymorphism, allele-specific oligonucleotide hybridization, PCR-single-strand conformation polymorphism, allele discrimination assay and Sanger sequencing. 1,3,[10][11][12][13][14][15][16][17][18][19][20] In addition to different detection techniques, differences in sample size may contribute to the wide range of KRAS mutation frequencies observed. The overall prevalence of KRAS mutations in the previous studies was 38% (150/400).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations